Factores en el consumo de alcohol en adolescentes - Cicua , Diana (2022)
The purpose of this report of quantitative, trans-sectional and correlational design was to describe the factors associated with alcohol consumption in adolescents of the city of Bogotá (Colombia). For this research, we employed a general data card to establish the general characteristics of alcohol consumption in the surveyed population and the Systematic Interview of Alcohol Consumption to measure the categories of personal situations and situations involving others. These instruments were applied to 406 adolescents between 12 and 17 years old from both genders belonging to social strata 4 and 5 of five urban locations in Bogotá (Colombia). Personal situations were found to be the principal risk factors in adolescents, rather than those involving interaction with others.